2016
DOI: 10.17665/1676-4285.20165251
|View full text |Cite
|
Sign up to set email alerts
|

Validação de protocolo para pessoas com úlcera venosa: composição e critérios de avaliação

Abstract: Aims:  to  confirm  and  refine  the  multidisciplinary  care  protocolstructure   for   people   with   venous   ulcers   treated   in   primary   care.   Method:   a methodological,  quantitative  study,  carried  out  in  three  steps:  development  of  the instrument from the literature review; and validation of the content, through the Delphi technique  in  two  stages:  one  with  51  judges  and  one  with  35.  The  analysis  used  the K appa index ≥0,81 and C ontent V alidity I ndex (C V I )> 0.80,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This was calculated using free and online software, the Online Kappa Calculator (8) , taking into account the "adequate with changes" indications for them. As acceptance criterion, concordance was higher than 0.65 among the judges, being considered good (9)(10) .…”
Section: Results Analysis and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was calculated using free and online software, the Online Kappa Calculator (8) , taking into account the "adequate with changes" indications for them. As acceptance criterion, concordance was higher than 0.65 among the judges, being considered good (9)(10) .…”
Section: Results Analysis and Statisticsmentioning
confidence: 99%
“…We also used the Content Validity Index (CVI), which measures the judges' agreement on the representativeness of the items in relation to the content under study. As acceptable, we considered indexes higher than 0.80 both for each unit assessment and overall course assessment (9)(10) .…”
Section: Results Analysis and Statisticsmentioning
confidence: 99%
“…The same process was used in a doctoral thesis to develop a protocol for care of people with venous ulcers in primary care. The article found that the Delphi technique was advantageous for being flexible and valuing the opinion and knowledge of the participating experts, allowing reflection on the behavior of professionals and the standardization of protocol to meet the needs of persons with venous ulcers (Costa, 2013).…”
Section: Pulmonary Hypertension Affects 25 Million People Worldwide (...mentioning
confidence: 99%
“…It is understood that the validation of protocols and instruments with the Delphi technique is positive and can be used in order to consensually bring together actions that must be standardized in care, improving the quality of care for both professional practice and patients (Costa, 2013). The need for the development and validation of a care protocol for patients with PH is pointed out through the evaluation by specialists of items that are believed to be relevant.…”
Section: Pulmonary Hypertension Affects 25 Million People Worldwide (...mentioning
confidence: 99%